Experimental Study on Physicochemical and Mechanical Properties of Mortar Subjected to Acid Corrosion - Runke Huo; Shuguang Li; Yu Ding (Advances in Materials Science and Engineering)
The 28 days cured cement mortar samples were soaked in HCl (pH = 1 and 2) and H2O (pH = 7) solutions for 90 days. By monitoring the ion concentration of H+ and Ca2+ and measuring the changes in weight loss, longitudinal wave velocity, and uniaxial compressive strength values of the corroded mortar, the physicochemical and mechanical properties of the mortar specimens were studied. Experimental results indicate that the process of the mortar sample subjected to HCL erosion has apparent stage characteristics. In the initial stage of corrosion, the chemical reaction increased the porosity of the specimen, which leads to the decrease of longitudinal wave velocity of the samples. At the same time, the corrosion solution continuously penetrates into the mortar pore system, which leads to the increase of the mass, and it is considered that the diffusion process plays a leading role during this period. Moreover, the colloidal compounds generated by the chemical reaction can not only fill the pore space but also block the continuous reaction, which led to the increase of the longitudinal wave velocity of the specimen. With the prolonging of corrosion time and infiltration path, the pH value and the concentration of Ca2+ tend to be stable, the diffusion action is weakened, and the chemical reaction is continuous, which led to the decrease of the mass and wave velocity gradually. It is considered that the chemical reaction plays a leading role in this process. Based on the induction and analysis of the test results, a generalized porosity model regarding the increase of the porosity and the decrease of effective bearing area of the mortar sample was proposed. The relation between the uniaxial compressive strength and the corrosion time of the corroded mortar is deduced, and the unknown parameters are determined based on the regression analysis of the test data.